Глобальна е-комерція: від інновацій до соціальних мереж - Тебенко, Віта Миколаївна; Завадських, Ганна Миколаївна; Лисак, Оксана Іванівна; Tebenko, Vita; Zavadskykh, Hanna; Lysak, Oksana (Запоріжжя : Видавничий дім «Гельветика», 2024)
UA: У статті розглядається сучасний стан електронної комерції на світовому рівні, проаналізовані глобальні тенденції, ринкові показники та актуальні тренди. Автори надають уявлення про ключові показники ринку. Особливу увагу приділено купівельній поведінці онлайн-покупців та показникам конкуренто-спроможності бізнесу. Висвітлені актуальні тренди електронної комерції на 2024 рік, такі як розвиток мобільної та соціальної комерції, та їх вплив на бізнес-моделі в умовах постійних технологічних змін. /// EN: The purpose of the study is to analyze the current state of e-commerce at the global level, highlight global trends and prospects for further development, taking into account challenges. The scientific novelty of the work is revealed in a comprehensive analysis of recent changes in the structure and functioning of the global e-commerce market. The article highlights current trends in e-commerce. The practical value of the article consists in the formation of recommendations for businesses on adaptation to new realities, such as the use of social networks to stimulate sales, optimization of mobile platforms and consideration of sustainable development. Main results. The work presents the key indicators of the global e-commerce market, in particular, the volume of sales, market growth. The authors of the study focus on the purchasing behavior of online shoppers, noting that factors such as convenience, accessibility and speed of the process have recently had a significant impact on the purchase decision. The increase in the use of mobile phones and applications, the growing popularity of social commerce (social platforms for selling goods) remain the main factors in the development of the sector. The integration of mobile payment systems, the optimization of purchases through mobile phones and the use of social media create new opportunities for businesses and consumers. It has been established that the key factors of business competitiveness are service personalization, process automation, and business adaptation to changes in consumer behavior. At the same time, businesses are focusing on environmental initiatives such as reducing waste and using energy-saving technologies, which is setting new standards for sustainable development.
Global e-commerce: from innovation to social networks
Keywords: електронна комерція; цифровізація; цифрова економіка; цифрова трансформація; соціальна комерція; мобільна комерція; онлайн-покупці; e-commerce; digitization; digital economy; digital transformation; social commerce; mobile commerce; online shoppers